Nitrogen-doped Biomass Carbon Coupled with Copper Oxide Materials for Electrocatalytic Reduction of CO2 - GUO Tianyu; ZHANG Jianing; BAI Dehao; ZHANG Jinnan; QI Yu; WANG Hongtao (Taiyuan Ligong Daxue xuebao)
[Purposes] Electrocatalytic technology for converting CO2 into high-value-added fuels and chemicals has promising applications. However, developing electrocatalysts with superior performance still faces significant challenges. [Methods] In this study, wheat bran was used as the precursor of biomass carbon and the pyrolysis method was used to prepare nitrogen-doped biomass carbon materials (NC). By further coupling with CuO via a hydrothermal method, a series of CuO@NC composite materials were costructed. The crystalline phase, microscopic morphology, structure, and elemental valence states were analyzed by multiple characterization techniques. The electrocatalytic performance was investigated towards the electrocatalytic reduction of CO2. [Findings] Results indicate that the composite catalyst synthesized at 160 ℃ (CuO@NC-160) exhibits high selectivity towards ethylene, with a maximum faradaic efficiency of 26.85% at -1.18 V vs. RHE. This study presents a feasible pathway for fabricating low-cost and efficient CuO-based electrocatalysts.